2009
DOI: 10.1016/j.humimm.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Aging is associated with a numerical and functional decline in plasmacytoid dendritic cells, whereas myeloid dendritic cells are relatively unaltered in human peripheral blood

Abstract: Dendritic cells (DC) are potent antigen-presenting cells that initiate and regulate T-cell responses. In this study, the numbers and functional cytokine secretions of plasmacytoid and myeloid DC (pDC and mDC, respectively) in peripheral blood from young and elderly subjects were compared. Overall, pDC numbers in peripheral blood were lower in healthy elderly compared with healthy young subjects (p = 0.016). In response to influenza virus stimulation, isolated pDC from healthy elderly subjects secreted less int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
200
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(242 citation statements)
references
References 46 publications
31
200
1
3
Order By: Relevance
“…They produce copious amounts of IFN-I very early in the infection. We (Sridharan et al 2010) and others (Canaday et al 2010;Jing et al 2009;Shodell and Siegal 2002;Stout-Delgado et al 2008;Qian et al 2011) have reported decreased production of IFNs by pDC population in the aged subjects. In addition to pDC, the myeloid dendritic cells (mDCs) subset is also capable of producing IFNs in response to viral infection.…”
Section: Introductionmentioning
confidence: 53%
“…They produce copious amounts of IFN-I very early in the infection. We (Sridharan et al 2010) and others (Canaday et al 2010;Jing et al 2009;Shodell and Siegal 2002;Stout-Delgado et al 2008;Qian et al 2011) have reported decreased production of IFNs by pDC population in the aged subjects. In addition to pDC, the myeloid dendritic cells (mDCs) subset is also capable of producing IFNs in response to viral infection.…”
Section: Introductionmentioning
confidence: 53%
“…A phenomenon has been reported in children during the first decade of life that their pDCs numbers decline rapidly whereas the numbers of mDCs remain relatively stable (20,21). There are at least three studies demonstrated an age-related decline of pDC (22)(23)(24) but two other studies showed no changes (19,25). Conflicting findings have also been reported with regard to the age-related changes in mDCs.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] However, the molecular mechanisms responsible for these changes in aged mice have not been thoroughly investigated. Considering that Wnt5a expression was elevated in aged hematopoietic precursors and functioned as an important molecule in the aging of hematopoietic systems 25 , the deficiency in DC development in aged mice may also have been elevated due to the expression of Wnt5a.…”
Section: Introductionmentioning
confidence: 99%